Overview of the Massive Young Star-Forming Complex Study in Infrared and X-ray (MYStIX) project - Feigelson, E.; Townsley, L.; Broos, P.; Busk, H.; Getman, K.; King, R.; Kuhn, M.; Naylor, T.; Povich, M.; Baddeley, Adrian; Bate, M.; Indebetouw, R.; et al. (2013)
The Massive Young Star-Forming Complex Study in Infrared and X-ray (MYStIX) seeks to characterize 20 OB-dominated young clusters and their environs at distances d = 4 kpc using imaging detectors on the Chandra X-ray Observatory, Spitzer Space Telescope, and the United Kingdom InfraRed Telescope. The observational goals are to construct catalogs of star-forming complex stellar members with well-defined criteria and maps of nebular gas (particularly of hot X-ray-emitting plasma) and dust. A catalog of MYStIX Probable Complex Members with several hundred OB stars and 31,784 low-mass pre-main sequence stars is assembled. This sample and related data products will be used to seek new empirical constraints on theoretical models of cluster formation and dynamics, mass segregation, OB star formation, star formation triggering on the periphery of H II regions, and the survivability of protoplanetary disks in H II regions. This paper gives an introduction and overview of the project, covering the data analysis methodology and application to two star-forming regions: NGC 2264 and the Trifid Nebula. © 2013. The American Astronomical Society. All rights reserved.